Analysis of Tax Collection Performance at the Bengkulu Pratama II Tax Service Office - Anek Duiana; Ummul Khair (Penerbit Jurnal Indonesia, 2024)
The title of this research is Analysis of Tax Service Performance at the Bengkulu Pratama II Tax Service Office. Improving the quality of public services can be improved through improving service quality management, namely efforts to minimize the gap between service levels and consumer expectations. This research aims to determine the quantity, quality and timeliness of work in tax services at the Bengkulu Pratama II Tax Service Office. The object in this research at the Bengkulu Pratama II Tax Service Office. Meanwhile, the research subjects in this study were employees in the Service Section of the Bengkulu Pratama II Tax Service Office and taxpayers. Data collection techniques include interviews and literature study. Data analysis in this research is in the form of qualitative analysis, the results of this research can be concluded that the quantity of Tax service work at the Bengkulu Pratama II Tax Service Office is in accordance with the respective fields. For the quality of tax service work at the Bengkulu Pratama II Tax Service Office, the standard of employee work quality at the Pratama Tax Service Office is determined by statutory regulations. Meanwhile, punctuality of tax services at the Bengkulu Pratama II Tax Service Office was conducted by employees of the Pratama Tax Service Office to increase punctuality in paying taxes, achieving timely reporting on time and paying on time